Variations in Kindergarten Teachers' Cognitive Activations in Math-related Activities by Child Factors. Issue 1 (2nd January 2023) - Pan, Yue-Juan; Liu, Shan-Shan; Wang, Yu; Wu, Ni-Wen; Xie, Shuang
ABSTRACT: Research Findings: The present study analyzes whether child factors are linked to variations in teacher cognitive activation (CA) among individual children in math-related activities within Chinese kindergarten classrooms. The findings show that teachers tend to provide direct CA with high concreteness and that child engagement with tasks is significantly positively associated with the ratio of teacher CA to individual children. Moreover, a child's math ability is significantly negatively associated with both the ratio and overall contingency degree of CA that a child experiences. Practice or Policy: These results suggest that teachers should improve their knowledge and competence to adapt their teaching behaviors to child characteristics to provide children with high-quality and equitable math learning opportunities and that children should be taught to highly engage to obtain more proactive reactions from their learning environments.